Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1111/1469-7610.00771
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Memory and Cognitive Ability in Children Born Very Prematurely

Abstract: In light of recent reports of episodic memory difficulties linked to early childhood hypoxia (Isaacs et al., 2000; Vargha‐Khadem et al., 1997), preliminary findings of everyday memory function are reported for 20 children born at or before 32 weeks gestation, compared to 20 children born at term. Memory skills were assessed using the Rivermead Behavioural Memory Test for Children (Wilson, Ivani‐Chalian, & Aldrich, 1991) at 5 years of age. Everyday memory problems were not found to be a general feature of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 28 publications
7
37
1
10
Order By: Relevance
“…The results regarding memory coincide with those of Briscoe, Gathercole, and Marlow (2001) who observed deficits in premature five year olds.…”
Section: Discussionsupporting
confidence: 88%
“…The results regarding memory coincide with those of Briscoe, Gathercole, and Marlow (2001) who observed deficits in premature five year olds.…”
Section: Discussionsupporting
confidence: 88%
“…In relation to cognitive development, the research found global cognitive delays in children born prematurely, but the specific cognitive processes most affected are memory from 2 to 6 years (40,42,43,45,47,48,52), attention from the first year of birth (35,36,38,41,44) and visual-spatial processing at 3-4 years (42,43,45). However, there is no consensus on the degree of impairment of memory and executive function, because some studies find they are not affected in the first 2 years (37), and other studies find worse scores at 5 and 6 years (48, 52).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on communicative -linguistic development found that preterm children have problems in auditory discrimination in the first days of life, and at 4 and 5 years old (53,55,62), problems in grammar skills at 2, 3, 5 and 6 years old (47,50,55,57,59,61,64), problems in naming objects and words at 4 and 5 years old (55,62,63,64) and pre-reading skills at 6 years (64). Other studies found that these children have no problems in lexical production at 4 years old (62).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations